Resilience and recovery potential of duneland vegetation in the southern Kalahari. Issue 1 (10th January 2014) - Bhattachan, Abinash; D'Odorico, Paolo; Dintwe, Kebonyethata; Okin, Gregory S.; Collins, Scott L.
Abstract : Many dune fields around the world have undergone alternating periods of mobilization and stabilization in response to changes in wind power and rainfall. However, in modern times disturbances associated with land use are believed to be a dominant factor contributing to the activation of stabilized vegetated dunes in drylands, while the reduction in human activities such as grazing and farming may lead to stabilization of once active dune fields. The Kalahari region of southern Africa has recently begun to exhibit visible signs of dune mobilization, a process that could lead to an activation of aeolian transport in the region with important implications for the biogeochemistry of downwind terrestrial and marine ecosystems. It is still unclear whether the region is poised at a tipping point between its current state (i.e., vegetated fixed linear dunes), and a "degraded" state (i.e., barren and active dunes). Here we investigate the ability of the landscape to recover from the degraded state by assessing the resilience of duneland vegetation and evaluating the vegetation and soil characteristics. Using field observations and soil seed bank experiments, we show that palatable perennial grass cover is reduced while the seedbank is depleted on grazed dunefields. Conversely, the interdunes generally exhibit relatively rich seed banks. Soils from grazed and ungrazed sites show that plant available nutrient contents are not significantly different; therefore, soil nutrients are likely not a major factor limiting the recovery of perennial vegetation in this region. It is observed that the perennial grasses reestablish on the recovering dunes after grazers have been excluded, indicating that the landscape is still able to recover after years of denudation and that any irreversible shift to a stable degraded state is likely during extended periods of disturbance and/or climatic shifts that promote the degraded state. We also find that changes in grass cover, grass community composition, and seed bank can serve as indicators of whether the system has irreversibly shifted from a vegetated to a bare dune state.